Metric study on depth of the sigmoid sinus plate in relation to suprameatal (Macewen's) triangle (Iraqi Journal of Medical Sciences, 2016)
Background: The lateral wall of the mastoid antrum, which offers the usual surgical approach to the tympanic cavity, is formed by the postmeatal process of the squamous part of the temporal bone. Since the suprameatal triangle covers the lateral wall of the mastoid air system, it is of importance to otologic surgeons during mastoidectomy.Objectives: To examine the relationships of the surgical landmarks on the lateral surface of the mastoid bone with the landmarks in a deeper location. Morphometric measurements were performed between the surgical landmarks (Macewen's triangle) and the sigmoid sinus plate.Methods: 30 dry human adult skulls were investigated. Three marks were allocated on the left and right sides of the norma lateralis of these skulls namely the tip of the mastoid process, the asterion, and the region of the suprameatal triangle (posterior border).Results: The measurements of (D1+D2), (D1+D3) and (D2+D3) showed statistical significant differences. The correlations of D1, D2 and D3 on the right and left sides showed statistical significant differencesConclusion: The assessment of the depth of sigmoid sinus plate may be used as a mark that possibly point toward avoidance of the bleeding possibility during mastoidectomy. The suprameatal approach eliminates the need for mastoidectomy and avoids the damage of sigmoid sinus plate. If the depth can be assessed by measuring D1 and D2 on lateral X-rays of the heads as this study prove that we can avoid the dangerous complications which occur in the normal mastoidectomy. Keywords: Suprameatal triangle, mastoidectomy